A Systematic Review of Data Visualization - Balan, Shilpa (Journal of Strategic Innovation and Sustainability, 2024)
Data visualization involves presenting data in graphical or pictorial form that in turn helps with decision support. This study addresses the importance of data visualizations in today’s data world, and its role in effective communication in various industry sectors. This study applied the PRISMA methodology to conduct the literature review. Four major themes are identified in this paper: data visualization principles, methods, contemporary chart types, and data visualization challenges. Popularly applied data visualization principles such as Gestalt Principles that help make data visualizations more effective are examined. Advanced chart types include doughnut chart, chord diagram, sankey diagram, and violin plot. Some challenges associated with data visualizations are data accuracy, complexity and uncertainty. Given the challenges, visualizations still benefit any field of study that requires interpreting and presenting complex information.